A community-based friendly health clinic: An initiative adolescent reproductive health project in the rural and urban areas of Indonesia - Tantut Susanto; Iis Rahmawati; Wantiyah (Elsevier, 2016)
Objective: This study aims to examine the effects of a community-based friendly health clinic (CFHC) program that adopts manual participatory learning (MPL) intervention on the adolescents living in the rural and urban areas of Indonesia to gain further insights into their knowledge, attitudes, and skills related to adolescent reproductive health (ARH). Methods: A quasi-experimental design was used to obtain information on the ARH knowledge, attitudes, and skills of adolescents. Two intervention studies that used similar protocols and measures were conducted. A total of 192 adolescents (96 adolescents from urban and rural areas) participated in the project, and the participants from each area were divided into eight groups. A questionairre was adopted to measure the ARH knowledge, attitudes, and skills of these participants. A content analysis of the logbook entries of these respondents was conducted to identify their ARH-related problems. The questionnairre and self-reported ARH data were collected before and after the eight-week program. Results: The CFHC program significantly increased the ARH attitudes (p = 0.045) and skills (p = 0.009) of adolescents in the rural area, but only improved the ARH knowledge (p < 0.001) of adolescents in both rural and urban areas. Fourteen themes were identified in three dominant categories, namely, schools, families, and communities. Conclusions: The CFHC with MPL intervention can improve the ARH knowledge, attitudes, and skills of adolescents in the rural area, but can only improve the ARH knowledge of adolescents in the urban area. The ARH program must be designed based on the characterictics of these adolescents to improve their life skills during puberty.